Effects of Political Connections on Accounting Conservatism, Investment Efficiency and Cost of Financing - Seyyed Kazem Ebrahimi (Ph.D) (Shahid Bahonar University of Kerman, 2020)
Objective: This study aimed to examine the effects of Political connections on accounting conservatism, investment efficiency and cost of financing in the companies listed in the Tehran Stock Exchange during the period 2013 to 2017. Method: Data was collected using document mining method and referring to the databases, and data analysis method was inferential. Eviews software was used to provide estimates for the concerning variables. The panel data model was used to test the research hypotheses. Results: The findings of the research indicated that political connections in the the companies have negative and significant effects on accounting conservatism, and have negative and significant effects on cost of financing. Also, according to the research findings, company's political connections do not have significant impacts on capital efficiency. Conclusion: As the debt ratio of corporation increases, the level of conservatism decreases. This means that companies that have political connections are less conservative than other companies.